Is there evidence of vertical transmission of variant Creutzfeldt–Jakob disease?. Issue 7 (27th April 2009) - Murray, Katy; Peters, James; Stellitano, Lesley; Winstone, Anne Marie; Verity, Christopher; Will, Robert G
Abstract : Objectives: The possibility of vertical transmission of variant Creutzfeldt–Jakob disease (vCJD) has been raised because of the widespread distribution of infectivity in vCJD and the demonstration that this condition can be transmitted through blood transfusion. The aim of this study is to search for evidence of this type of transmission of vCJD. Methods: A national surveillance system for CJD has been established in the UK since 1990. Through this register, details were extracted of all children born to vCJD cases up to March 2009. This list was checked against the CJD register and cases identified through the UK study of Progressive Intellectual and Neurological Deterioration in children to determine whether any of the children of vCJD cases had themselves developed a progressive neurological disorder or vCJD. Results: 125 children were born to parents with a diagnosis of vCJD. Nine of these children were born to females with vCJD who were symptomatic at conception, birth or within a year of clinical onset. Only one woman was known to have breast fed her child. None of the children of vCJD cases have been referred to the National CJD Surveillance Unit as suspected vCJD and none have been classified as suffering from a progressive neurodegenerative disorder through the Progressive Intellectual and Neurological Deterioration study. One of the children has been investigated by the National Prion Unit (see accompanying case report). Interpretation: To date there is no evidence of vertical transmission of vCJD. However, the incubation period through this mechanism might be prolonged and it will be many years before observational data can exclude this possibility.